2022
DOI: 10.1111/anae.15819
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐operative management of transgender patients: time for some guidance?

Abstract: merely a probability order and should be interpreted with caution, as the differences in probability of being superior are small. One advantage of network meta-analysis is that it evaluates all the treatments on a common scale. Clinicians all registered attendees, which comprised 58% (53/92) consultants, 40% (37/92) trainees and 2% (2/92) specialty or specialist grade doctors. All survey respondents gave consent for publication of their data. The survey results were as follows:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Our recent educational session for the Association of Anaesthetists demonstrated that clinicians' confidence in managing transgender patients can be significantly and rapidly increased. 6 Further work on the subject, its inclusion in undergraduate and postgraduate curriculums, ongoing training and the development of national guidelines are all likely to be key in driving transgender healthcare forward.…”
Section: What Are the Next Steps?mentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent educational session for the Association of Anaesthetists demonstrated that clinicians' confidence in managing transgender patients can be significantly and rapidly increased. 6 Further work on the subject, its inclusion in undergraduate and postgraduate curriculums, ongoing training and the development of national guidelines are all likely to be key in driving transgender healthcare forward.…”
Section: What Are the Next Steps?mentioning
confidence: 99%
“…86% of respondents stated they felt postgraduate bodies should deliver education on transgender healthcare. 6 To date, these needs are not addressed in the Faculty of Intensive Care Medicine (FICM), Royal College of Anaesthetists (RCoA), Royal College of Emergency Medicine (RCEM) or Royal College of Physicians (RCP) curricula throughout any stage of training. 7–10 Improving our means of recognising, understanding and addressing the needs of transgender patients is a central factor in our ability to provide optimal care.…”
Section: Introductionmentioning
confidence: 99%
“…We were prompted to consider whether patients taking testosterone as a gender-affirming treatment could be similarly affected. The number of transgender people in the United Kingdom has increased in the last decade [2].…”
mentioning
confidence: 99%
“…One of the most surprising findings from the survey were some of the responses from senior doctors, including: 'I believe in biology not ideology', 'How would I opt out of treating a transgender patient', and 'I would refuse to treat a transgender patient undergoing elective surgery'. 5 Such discrimination is illegal under the Equality Act 2010. 7 These comments may represent the tip of a transphobic iceberg and highlight just how important it is to energise education for change.Estimates of the number of openly transgender patients in the UK vary from 200,000 to 600,000, with numbers increasing year on year.…”
mentioning
confidence: 99%
“…4 Our recent survey on UK anaesthetists suggested it may be even more than this, with the median confidence regarding the perioperative care of transgender patients being 3/10. 5 As discussed in our recent review article in the journal, 6 many of the specific considerations for transgender patients are relevant to critical care (alterations to airway anatomy, cardiovascular and respiratory changes, the management of hormone therapy etc. ), and it would therefore be logical to extrapolate that a similar knowledge gap exists in this domain.…”
mentioning
confidence: 99%